MONITORING OF WORKERS AND PRODUCT MARKET COMPETITION: THE ROLE OF WORKS COUNCILS. (30th December 2014) - Gürtler, Oliver; Höffler, Felix
<x xml:space="preserve">Abstract</x> Often the consent of worker representations, such as works councils, is required before firms are allowed to install technologies that monitor workers' behavior. Absent monitoring, workers produce low output, while at the same time receiving an information rent. To gain the works council's consent to the installation of a monitoring technology, firms need to compensate workers for the lost information rent. Hence, by making it more costly to produce high output, works councils can serve firms as an instrument to commit to low output levels. This provides a rationale for why works council rights are not opposed more strongly by employers. (JEL D43, D86, J83, L13)